Dectin-1 deficiency does not affect atherosclerosis development in mice. Issue 2 (April 2015) - Szilagyi, Katka; Gijbels, Marion J.J.; van der Velden, Saskia; Heinsbroek, Sigrid E.M.; Kraal, Georg; de Winther, Menno P.J.; van den Berg, Timo K.
Abstract: Objective: Recent data suggest the involvement of dectin-1 in atherosclerosis through regulation of local reactive oxygen species production. The aim of the current study was to assess the effect of dectin-1 deficiency on atherosclerotic plaque development. Methods: Using immunohistochemistry dectin-1 expression was observed on foamy macrophages in atherosclerotic lesions in mice. Following lethal irradiation LDLR −/− mice were reconstituted with bone marrow from either wild type or dectin-1 −/− mice. After recovery, mice were fed a high fat diet for 9 weeks and atherosclerotic lesions were analyzed. Results and conclusion: Overall, we found no significant differences in plaque size or severity between the groups. Also no differences were observed in granulocyte or macrophage composition of the plaques or in the ability to produce reactive oxygen species by macrophages from both groups. Dectin-1 is dispensable for the development of atherosclerotic lesions in mice. Graphical abstract: Highlights: Hematopoietic dectin-1 deficiency has no effect on atherosclerotic lesions in mice. Mouse macrophages fail to respond to vimentin. Dectin-1 is dispensable for development of atherosclerosis.